Comparative assessment of autologous and allogeneic iNKT cell transfer in iNKT cell-based immunotherapy - Takami, Mariko; Motohashi, Shinichiro (Frontiers in Immunology, 2024)
Invariant natural killer T (iNKT) cells are a small subset of T lymphocytes that release large amounts of cytokines such as IFN-γ and exhibit cytotoxic activity upon activation, inducing strong anti-tumor effects. Harnessing the anti-tumor properties of iNKT cells, iNKT cell-based immunotherapy has been developed to treat cancer patients. In one of the iNKT cell-based immunotherapies, two approaches are utilized, namely, active immunotherapy or adoptive immunotherapy, the latter involving the ex vivo expansion and subsequent administration of iNKT cells. There are two sources of iNKT cells for adoptive transfer, autologous and allogeneic, each with its own advantages and disadvantages. Here, we assess clinical trials conducted over the last decade that have utilized iNKT cell adoptive transfer as iNKT cell-based immunotherapy, categorizing them into two groups based on the use of autologous iNKT cells or allogeneic iNKT cells.